2021
DOI: 10.1177/10935266211008438
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Malignant Peritoneal Mesothelioma Mimicking an Autoinflammatory Syndrome in a 12-Year-Old Boy

Abstract: A case of a malignant peritoneal mesothelioma mimicking an autoinflammatory syndrome in a 12-year-old boy is reported. The patient initially presented with lymphadenopathy and weight loss but without abdominal pain. Three things confounded the initial diagnosis: a positive test result for a gene related to cryopyrin-associated periodic syndrome, a positive response to the autoinflammatory syndrome treatment, and a lymph node biopsy which showed “hyperplastic mesothelial cells in the lymph sinuses.” His symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…14 Given the relatively nonspecific initial symptoms, patients occasionally receive an initial alternative diagnosis, including Whipple disease, tuberculosis, mesenteric lymphangioma, other malignancies, or an infectious/inflammatory peritoneal disease. In addition, 2 cases have been reported in which malignant peritoneal mesotheliomas in 2 teenage patients were clinically misdiagnosed as an autoinflammatory syndrome, 15 and inflammatory bowel disease, 16 respectively.…”
Section: Symptomsmentioning
confidence: 99%
See 4 more Smart Citations
“…14 Given the relatively nonspecific initial symptoms, patients occasionally receive an initial alternative diagnosis, including Whipple disease, tuberculosis, mesenteric lymphangioma, other malignancies, or an infectious/inflammatory peritoneal disease. In addition, 2 cases have been reported in which malignant peritoneal mesotheliomas in 2 teenage patients were clinically misdiagnosed as an autoinflammatory syndrome, 15 and inflammatory bowel disease, 16 respectively.…”
Section: Symptomsmentioning
confidence: 99%
“…8 However, cases of mesothelioma associated with asbestos in young adults have been reported in the literature, starting with asbestos exposure between 6 and 11 years of age, with a latency period of 11 to 34 years before the development of the disease, resulting in only 3 pediatric cases with a possible association between asbestos exposure and mesothelioma, out of the > 300 pediatric cases reported in the literature. 15,19 In a series of 80 pediatric patients with mesothelioma, Fraire et al 10 reviewed possible risk factors and found only 4 children who had exposure to known risk factors (2 had a history of exposure to asbestos, 1 had received radiation therapy, and 1 was exposed to isoniazid in utero). Only 3 pediatric patients who had previous malignancies, including acute leukemia, nephroblastoma, and inflammatory myofibroblastic tumor, have been described.…”
Section: Imagingmentioning
confidence: 99%
See 3 more Smart Citations